2016
DOI: 10.1039/c6ta06213j
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing polymers and composites for extreme environments

Abstract: The first self-healing polymers and fiber reinforced composites with temperature stability beyond 240 °C and high healing efficiencies are developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…However, there are some challenges for the self-healing function based DA reaction, for example, the number of groups for DA reaction is limited, as well as low application temperature (120 °C) during DA reaction is one of the major demerits. [86,117] Therefore, further investigation about DA reaction is critically important to optimize and achieve better self-healing surface materials.…”
Section: Self-healing Based On Reversible Covalent Bondsmentioning
confidence: 99%
“…However, there are some challenges for the self-healing function based DA reaction, for example, the number of groups for DA reaction is limited, as well as low application temperature (120 °C) during DA reaction is one of the major demerits. [86,117] Therefore, further investigation about DA reaction is critically important to optimize and achieve better self-healing surface materials.…”
Section: Self-healing Based On Reversible Covalent Bondsmentioning
confidence: 99%
“…Thermal stability at high temperatures is as important as low-temperature cleavage for self-healing polymers and composites. Heo et al [29] reported that a self-healing polymer based on the DA reaction and its composite achieved a 94% and 69% healing efficiency, respectively, while the polymer was stable at 240 • C. Effective thermal stability with mechanical strength that is comparable to other engineering polymers and structural composites will be beneficial for the future of self-healing composite materials.…”
Section: New Materials and Approachesmentioning
confidence: 99%
“…This can be achieved by changing the chemical structure of the DA groups. A recent example involves the use of anthracene and maleimide groups [52] (Figure 11). The resulting polyurethanes (PU) show self-healing behavior by pure DA reaction for mechanically cleaved adducts.…”
Section: Nanocomposites -Recent Evolutionsmentioning
confidence: 99%